Neonatal gastric perforation secondary to a strangulated congenital diaphragmatic hernia - Alaa Obeida; Nouran Abdelmoemen; Nancy Ibrahim; Sayed Khedr; Aly Shalaby (Elsevier, 2018)
Congenital diaphragmatic hernia (CDH) occurs as 1/3000-1/4000 live births. The main pathology associated with the diaphragmatic defect is pulmonary hypoplasia and hypertension. Occasionally gastrointestinal symptoms may also be present due to obstruction and incarceration of herniated bowel loops. Here we present a case of a term male neonate with an antenatal diagnosis of CDH. While on the intensive care unit he developed symptoms of acute bowel obstruction on day 14 of life. An emergency laparotomy was done with a partial gastrectomy for gastric perforation. A concomitant splenectomy was carried out due to an iatrogenic injury. The defect was closed primarily. The patient made a full recovery and was discharged on day 27 post operatively. Keywords: Gastric necrosis, Bowel obstruction, Kasr Al Ainy, Egypt